Anti-proliferative potential of Eleutherine bulbosa (Mill.) urb. bulb extracted under optimised condition on three-dimensional retinoblastoma cell culture model (weri-Rb-1) - Kamarudin, 'Ammar Akram (2022)
According to the Malaysia National Cancer Registry (2007-2011), ocular cancer has been listed among the most prevalent cancers in children after leukaemia, brain and nervous system, lymphoma, as well as bone. A paucity of scientific evidence on the mode of retinoblastoma inhibition remains a great challenge. A folklore medicine locally used among the Dayak community, “Bawang Dayak” or scientifically known as Eleutherine bulbosa bulb has been chosen as a potential alternative remedy to inhibit the growth of retinoblastoma. Therefore, the main objective of this study is to scrutinise the new insights on anti-proliferative potential of E. bulbosa bulb extract against the mode of retinoblastoma inhibition. The optimisation of the phenolic extraction using response surface methodology was carried out and the results revealed that the temperature of 48 °C; time of 70 min; solid-liquid ratio of 10 g in 146 mL was the best for phenolic extraction. High Performance Liquid Chromatography (HPLC) analysis revealed that eight bioactive compounds were successfully quantified such as gallic acid, chlorogenic acid, rutin, quercetin, epicatechin gallate, eleutherin, kaempferol, and myricetin. The results of the cytotoxic study revealed a potent IC50 value of 15.7 ± 2.7 μg/mL compared to cisplatin with 3.6 ± 2.2 μg/mL. The acridine orange/ propidium iodide (AO/PI) dual staining illustrated a significant apoptotic cell death, manifesting apoptotic features such as membrane blebbing, chromatin condensation, and secondary necrosis. In the meantime, Annexin V-FITC portrayed early and late apoptosis as well as cell cycle arrestment in Sub G0/G1 and G0/G1 phases on WERI-Rb-1 cells upon treatment. The apoptosis was further confirmed with qPCR analysis, demonstrating an upregulation of Bax, Bad, p53, Caspase 3, Caspase 8, and Caspase 9. The downregulation of Bcl-2, Bcl-xL, Nrf-2, and HO-1 genes confirmed the apoptotic and antioxidant related pathways were involved in the mode of retinoblastoma inhibition. To further elucidate and compare its anti-proliferative potential, 3D cell culture studies were conducted to investigate the effect of E. bulbosa ethanolic bulb extract on apoptotic mechanism and its relation to the antioxidant pathway. The cytotoxic assay was conducted by Resazurin sodium salt and demonstrated an increased IC50 value of 45.7 ± 1.7 μg/mL and 26.6 ± 6.0 μg/mL for E. bulbosa ethanolic bulb extract and cisplatin, respectively. The morphological assessments through 4’, 6-diamidino-2-phenylindole (DAPI) and PI double staining as well as scanning electron microscope (SEM) displayed the onset of apoptosis on the 3D retinoblastoma treated cells. The results of gene and protein expressions exhibited that the ratio of pro-survival and pro-apoptotic genes and proteins such as Bcl-2, Bcl-xL, Bax, and Bad were upregulated, suggesting that the extracellular matrix (ECM) hindered the drug penetration resulting in apoptotic resistance. However, the activation of caspase cascades like Caspase 3, 8, and 9 by E. bulbosa ethanolic bulb extract confirmed the intrinsic apoptotic mechanism pathway. Of note, the upregulation of antioxidant proteins for instance Nrf-2 and SOD-1 promotes the proliferation of WERI-Rb-1 cells and leads to tumour resistance due the presence of ECM. Surprisingly, the HO-1 protein was downregulated and may be potentially inhibited the growth of retinoblastoma upon treatment by mediating more reactive oxygen species (ROS). Taken together, these findings suggested that the ethanolic bulb extract of E. bulbosa may be potential anti-proliferative agent for retinoblastoma cancer as it portrayed selective killing properties in 3D WERI-Rb-1 cells as opposed to cisplatin. Besides, it provides a fundamental understanding on the inhibition of 3D retinoblastoma cancer cells as it mimics more tissue resemblance to in vivo conditions.